Implementation and secondary pharmaceutical patenting: patent data - Sampat, Bhaven N. (UK Data Service, 2016)
These are the data for two published articles, “Drug patenting in India: looking back and looking forward” (Nature Reviews Drug Discovery [NRDD], 2015) and "TRIPS implementation and secondary pharmaceutical patenting in Brazil and India" (Studies in Comparative International Development [SCID], 2015). The NRDD dataset includes the new drug application number, drug approval year, drug name (where available), and patent priority year (based on first patent) for new molecular entities approved by the U.S. FDA between 1995 and 2013. The SCID datasets include the patent application number, active ingredient, category (primary or secondary patent application), and the country specific outcome for each application. There are two files, one for Indian applications (scid_indianapplications.csv) and one for the Brazilian applications (scid_brazilianapplications.csv). This project analyses developing country strategies to limit the issuance of secondary patents in pharmaceuticals. Secondary patents can extend periods of exclusivity, delay generic entry, and contribute to high drug prices and reduced access to medicines. Accordingly, several developing countries have adopted policies to restrict the grants of such patents; such measures are widely promoted by analysts and international organisations alike. However, little is known about which countries are adopting what sorts of measures, and to what effect. The project develops a typology of approaches toward secondary patenting, and maps countries according to the typology. Empirical analyses focus on five countries with specific measures to limit secondary patenting and two without. The research involves assembling novel datasets of pharmaceutical patents filed in the seven countries, coding each application as primary or secondary, and examining outcomes for each application in each country. The analysis will not only generate cross-national data on grant rates for different types of drug applications, but also improve understanding of the effectiveness of different approaches to secondary patents. Quantitative analyses are complemented with case studies to reveal the social and political factors conditioning how patent policies work in practice.